Connections of the Economic, Ecological-Environmental and Social Functions of Rural Development in Communities Bordering the Hortobágy - Bainé Szabó, Bernadett (Acta Agraria Debreceniensis, 2004)
investigated the economic, ecological-environmental and social functions of rural development in communities bordering the Hortobágy National Park, such as in Balmazújváros, Hortobágy, Tiszacsege and Egyek. My purposes focused on four issues: (1) to work out a method on the basis of the examined and cited literatures, which defines the development of communities from economic, ecological and social aspects of rural development; (2) to reflect the changes in the role of agriculture; (3) to analyse the effects, advantages and disadvantages of Hortobágy National Park in relation to the economic, ecological and social lives of the examined communities; and (4) to make an economic analysis on the alternative income sources of Hortobágy, such as rural tourism, herb production and bio-farming in a family farm structure. When measuring the development of the communities I concluded that complex indexes hide the real consideration of the three functions of rural development and the possibility for comparing them on a community level. Furthermore, these 19 indicators are not enough to evaluate the situation, thus I raised the number of indicators and handled them on the basis of the three functions of rural areas. I classified the economic, ecological and social indicators into indicator groups within each functions, which make the determination of causes for underdevelopment possible. While only Tiszacsege and Egyek were considered to be backward on the basis of the complex index of the Hungarian Central Statistical Office, my investigations showed that even Balmazújváros and Hortobágy proved to be lagged behind from both economic and social aspects. The methodical development justified the hypothesis that few indicators are not enough to establish decisions objectively. New developmental orders emerged. Measuring development of communities may be all-rounded and more established by using this new method, which may result in objective preparation of decisions in rural development and more rational spreading of subsidies.